คุณลักษณะความเป็นพลเมืองดีในสังคมประชาธิปไตยของนักศึกษามหาวิทยาลัยแม่โจ้ - ผาเจริญ, วินิจ (วารสาร ศึกษาศาสตร์ มมร, 2018)
บทคัดย่อ การวิจัยครั้งนี้เป็นการศึกษาสำรวจคุณลักษณะความเป็นพลเมืองดีในสังคมประชาธิปไตยของนักศึกษามหาวิทยาลัยแม่โจ้ เพื่อเปรียบเทียบความคิดเห็นที่มีต่อคุณลักษณะความเป็นพลเมืองดีในสังคมประชาธิปไตยของจำแนกตามภูมิหลังของนักศึกษา และนำเสนอแนวทางการพัฒนาคุณลักษณะความเป็นพลเมืองดีของนักศึกษา กลุ่มตัวอย่างในการศึกษาได้แก่ นักศึกษาที่ลงทะเบียนเรียนในปีการศึกษา 2560 สาขารัฐศาสตร์และรัฐประศาสตศาสตร์ จำนวน 351 คน เครื่องมือที่ใช้ในการวิจัยคือ แบบสอบถามเรื่องคุณลักษณะความเป็นพลเมืองดีในสังคมประชาธิปไตย วิเคราะห์ข้อมูลด้วยสถิติเชิงพรรณนานา t-test และ One-Way ANOVA ผลการศึกษาพบว่า 1) นักศึกษามีคุณลักษณะความเป็นพลเมืองดีในสังคมประชาธิปไตยในภาพรวมที่ระดับมาก เมื่อพิจารณารายด้าน พบว่า นักศึกษามีคุณลักษณะความเป็นพลเมืองดีด้านคุณลักษณะพื้นฐาน รองลงมาคือ ด้านการเมืองการปกครองในสังคมประชาธิปไตย ด้านสังคมและวัฒนธรรม ด้านความรู้และทักษณะ ด้านเศรษฐกิจ 2) เปรียบเทียบคุณลักษณะความเป็นพลเมืองดีกับตัวแปรพื้นฐานจะพบว่า มีตัวแปรที่สามารถจำแนกความแตกต่างกันของคุณลักษณะความเป็นพลเมืองดีอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 คือ เพศ ภูมิลำเนา ชั้นปี และการอบรมเลี้ยงดูแบบประชาธิปไตยเท่านั้น ข้อเสนอแนะต่อการพัฒนาคุณลักษณะความเป็นพลเมืองดีในสังคมประชาธิปไตยมหาวิทยาลัยแม่โจ้ ได้แก่ 1) ควรจัดกิจกรรมการเรียนรู้ผ่านเวทีประชุม สัมมนาหรือกิจกรรมทางวิชาการและทำกิจกรรมร่วมกัน 2) ควรจัดให้มีการเรียนรู้ด้วยการบริการสังคม เพื่อเสริมสร้างความเป็นพลเมืองที่ดีในสังคมประชาธิปไตยทุกภาคการศึกษา 3) ควรเชิญหน่วยงานที่เกี่ยวข้างเช่น โรงเรียน วัด ชุมชน องค์กรปกครองส่วนท้องถิ่นและหน่วยงานต่างๆ เข้ามาถ่ายทอดองค์ความรู้เกี่ยวกับพลเมืองเพื่อให้เห็นว่าองค์กรเหล่านี้เป็นส่วนหนึ่งของมหาวิทยาลัยในการพัฒนาพลเมือง   Abstract This research is a survey based on studying the Characteristics of Good Citizenship in a Democratic Society of Students in Maejo University, in order to compare their opinions on the characteristics of good citizenship in democratic society by the background of students and present a guideline for developing the student characteristics of been a good citizen. The samples used in this study were; 351 students of public administration and political science who enrolled in the 2017 academic year. A questionnaire was used as a tool for gathering data in this research study based on the characteristics of good citizenship in democratic society. Data were analyzed using descriptive statistics, t-test and one-way ANOVA. The results of this study shows that: 1) Students have overall characteristics of a good citizen at high level.  Considering each aspect, it was discovered that, the students have good background in terms of their characteristics of been good citizens. Followed by, politics and governance rule of a democratic society, social and tradition, knowledge and economical characteristics, 2) compare the characteristics of a good citizen with the basic variables; the result shows that, there are variables that can statistically distinguish the features of good citizenship at significance level of 0.05. They include sex, place of birth, student year in the university and democratic upbringing. Suggestions for the developing characteristics of a good citizen in a democratic society of students in Maejo University are as follows: 1) organize some learning activities through conference, seminar or academic activity and also encourage doing some activities together. 2) Provide learning activities through their engagement on social services in order to enhance good citizenship in democratic society every semester. 3) Invite relevant agencies such as schools, temples, community organizations, local government agencies and others to give more knowledge about been a citizens, in order to enlighten and make them understand that these organizations are also part of the university in developing a good citizen.